Alder ingen hindring? - Kaare, Birgit Hertzberg (Tidsskrift for kulturforskning, 2004)
The point of departure of this article is the Norwegian computer party The Gathering. For three years the author was doing field research investigating a sub-culture developed by the computer enthusiasts connected to this annual event, using observations, interviews and a comprehensive qualitative questionnaire. The focus of this article is on the attitudes held by the computer enthusiasts towards the computer competence of their parents, teachers, grandparents and elderly people in general. The statements made by the youth are compared to the answers to another questionnaire sent to elderly people concerning their own computer skills. The article focuses on how hierarchical patterns between adults and adolescents are changed when children and young people have achieved skills in using digital media technologies which many adults do not master. The article gives an interesting view from the inside of the young computer enthusiasts' experiences of themselves, their self-images and their images of elderly people. The author discusses the influence of the powerful "Myth of the Competent IT-Child" on the views held by both young and old. In conclusion, the author claims that the high self esteeme - held by the young computer enthusiasts when it comes to digital competence - should be seen rather as a generational phenomenon than as a result of a life span experience, due to the fact that the generation growing up with the Internet has some historically unique experiences with digital technology.